Systematic literature review: Identification of students’ mathematical anxiety in mathematics learning - Woro Anglia Banda Sutomo; Dadang Juandi (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
Mathematics anxiety can be found at all levels of education, from elementary school to college students. This study aims to conduct a literature review related to mathematics anxiety in mathematics learning. The research method chosen in this study is the Systematic Literature Review. Data collection was carried out by documenting all articles that had similar research in this research report. The articles used in this study were 98 articles published for the period 2014–2022. The research was conducted at all levels of education. Based on the research results, there were 98 relevant articles published in 2014-2022 regarding mathematics anxiety in mathematics learning. It was noted that articles related to mathematical abilities including soft skills and hard skills dominated the number of articles. The collected articles mostly focus on research at the junior high school level, and researchers tend to prefer using quantitative research methods in their research.